Preferences of customers on different remittance centers in Digos City - Rase, Patrice Shainne; Celocia, Rizza Mae; Jagape, Karl (--Digos City: UM Digos College, 2017)
This study aimed to determine the preference of customers on different remittance centers in Digos City in terms of tangibility, assurance, responsiveness, reliability and empathy. The study used the descriptive method type of research. This study was conducted on different remittance center in Digos City namely, Mlhuilier Kwarta Padala Digos 1 branch, Mlhuilier Kwarta Padala Digos 3 branch, Palawan Express Pera Padala Roxas Ext. branch and Cebuana Lhuilier Digos 1 branch with a total of two hundred fifty five respondents. The profile of the respondent was also collected. Result of the survey showed that the most customer of remittance center in Digos city belong to the age bracket of 15-22 years old, there are more females than males, more single individual than married couple and widow, and the other (housewife, self-employed and unemployed) in the type of respondent has the highest frequency. The result also showed that there was no significant difference when analyzed by age, sex, marital status and type of respondent.